BRIEF REFLECTIONS ABOUT VOLUNTARY FORMALISM IN THE ITALIAN LAW SYSTEM - Di Fede, Antonio (Civitas et Lex, 2019)
The essay deals with the complex issue of voluntary formalism, regulated in the articles 1326 paragraph 4 and 1352 of the Italian Civil Code, and the exegetical problems connected to it. The study aims to verify whether the voluntary formalism occupies the same role or not and fulfills the same functions as the legal formalism. Then the relationship between the voluntary forms and the classic pathologies related to contracts has been investigated in order to verify the possibility of tracing the whole theme of the forms chosen by the parties within the different problem of the formation of the contractual agreement.